2009
DOI: 10.1088/0953-2048/22/9/095018
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting Fe1+δSe1−xTexthin films: growth, characterization and properties

Abstract: Thin films of Fe1+δSe1−xTex (δ∼0.18 and x∼0.5) have been successfully grown on (100)-oriented single-crystalline SrTiO3 and LaAlO3 substrates by pulsed laser deposition. The crystal structure was characterized by x-ray diffraction and the superconducting properties by electrical resistivity measurements. X-ray diffraction analysis establishes the growth of films with c-axis orientation. Atomic force microscopy showed a smooth surface morphology for the films grown on SrTiO3 substrates. All the films are ob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…For the 11 phase in particular, thin films are of interest due to the difficulties in making large, high quality single phase bulk samples of FeSe. Thin films of 11-phase have been extensively grown by pulsed laser deposition, 27,37,[43][44][45][46][47][48][49][50][51][52]85 molecular beam epitaxy 86 and sputtering. 57…”
Section: Additional Considerations For Thin Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the 11 phase in particular, thin films are of interest due to the difficulties in making large, high quality single phase bulk samples of FeSe. Thin films of 11-phase have been extensively grown by pulsed laser deposition, 27,37,[43][44][45][46][47][48][49][50][51][52]85 molecular beam epitaxy 86 and sputtering. 57…”
Section: Additional Considerations For Thin Filmsmentioning
confidence: 99%
“…Films grown on MgO, which has a large lattice parameter mismatch of about 10%, exhibit the best in-plane alignment. 57,41 The study by Yeh et al 32 in which epitaxial thin films were used to measure the effects of biaxial stress on the superconducting properties (along with many others 52,27,50 ) also shows that this superconducting phase is not strongly affected by lattice mismatch with the substrate. Lattice matching of the substrate with the a-axis of the Fe y (Se x Te 1-x ) phase can be said to play little part in texture development of the films, and superconductivity of Fe y (Se x Te 1-x ) films does not correlate with lattice mismatch.…”
Section: Substrate Choicementioning
confidence: 99%
“…Many studies on the film growth of FeSe 1Àx Te x have already been reported. [4][5][6][7][8][9][10][11] However, the question of what substrates are suitable for the growth of thin FeSe 1Àx Te x films remains controversial. For example, Kumary et al 6) reported that the T c value for the film on SrTiO 3 (STO) was higher than on LaAlO 3 (LAO).…”
mentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] However, the question of what substrates are suitable for the growth of thin FeSe 1Àx Te x films remains controversial. For example, Kumary et al 6) reported that the T c value for the film on SrTiO 3 (STO) was higher than on LaAlO 3 (LAO). In contrast, Han et al 7) reported an opposite result; the T c value on LAO was higher than that on STO.…”
mentioning
confidence: 99%
“…ron-based superconductors 1) possess attractive properties such as high critical temperatures (T c ) up to 56 K 2) and high upper critical magnetic fields >100 T, 3) which arouses active research to grow high-quality epitaxial films 4) in order to examine intrinsic properties and grain boundary properties, and to clarify the potential for device applications. In such circumstances, thin film growth of Fe-based superconductors such as fluorine-doped LnFeAsO (Ln = La, Nd), [5][6][7][8] cobalt-doped AEFe 2 As 2 (AE = Sr, Ba) [9][10][11][12][13][14][15] and Fe(S, Se, Te) [16][17][18][19][20][21][22][23][24][25][26][27][28][29] have been reported to date. Among them, cobalt-doped BaFe 2 As 2 (BaFe 2 As 2 :Co) epitaxial films have received much attention because of relatively easy growth by pulsed laser deposition (PLD) and high stability even in a moist atmosphere, 10) which are distinct advantages over LnFeAsO.…”
mentioning
confidence: 99%